Cover crop root attributes and their contribution to soil processes and agroecosystem sustainability - Luvina B. Madrid; Akanksha Sehgal; Rongzhong Ye; Kadambot H.M. Siddique; Kirsten Hein; Christopher Topp; Sruthi Narayanan (Agriculture, Ecosystems & Environment, 2026)

Breeding for high maize yields indirectly boosting root carbon in the US Corn Belt since the 1980s - Cintia Sciarresi; August Thies; Christopher Topp; Douglas Eudy; John L. Kovar; Slobodan Trifunovic; Philip M. Dixon; Sotirios V. Archontoulis (Field Crops Research, 2025)

Historical increases in plant density increased vegetative maize biomass while breeding increased reproductive biomass and allocation to ear over stem - Ezequiel Saenz; Alejo Ruiz; Cintia Sciarresi; Kyle King; Mitchell Baum; Antonella Ferela; Gerasimos J.N. Danalatos; Brenda Gambin; George Kalogeropoulos; August Thies; Raziel A. Ordóñez; Slobodan Trifunovic; et al. (Field Crops Research, 2025)

Cover crop cultivars and species differ in root traits potentially impacting their selection for ecosystem services - Kong M. Wong; Marcus Griffiths; Amelia Moran; Andrea Johnston; Alexander E. Liu; Mitchell A. Sellers; Christopher N. Topp (Plant and Soil, 2024)
Background and aims Cover crops have the potential to aid in adapting agricultural systems to climate change impacts through their ecosystem services, such as preventing soil erosion, remediating soil structure, and storing carbon belowground. Though roots are integral to these processes, there is a lack of cover crop root trait data. This study aims to characterize rooting behavior of several commercially available cover crops and assess how differences in root system architecture potentially impact their selection for ecosystem services. Methods Twenty-two cover crop cultivars across the grass, legume, and brassica families were grown in O’Fallon, Missouri, USA. Canopy cover was monitored throughout the growing season. Shoot and root biomass samples were collected and analyzed. Results Cereal rye and winter triticale were the most winter hardy cultivars and provided the highest percent canopy cover. Cereal rye and winter triticale also generated the highest amount of shoot and root biomass among treatments but diverged in their root system architectures. Winter triticale forms coarser roots and exhibited deeper rooting, which may be better suited for carbon sequestration. Rapeseed and Siberian kale have favorable C:N ratios for nutrient recycling, but rapeseed may invest more into lateral root formation and have a higher potential to “catch” excess nutrients. Conclusion Selection of cover crops for ecosystem services should account for root system architecture and their suitability for these ecosystem services. Differences in root traits among cultivars within the same family highlight the potential to breed cover crop root system architecture to further enhance ecosystem service efficacy.

Harvest index has increased over the last 50 years of maize breeding - Alejo Ruiz; Slobodan Trifunovic; Douglas M. Eudy; Cintia S. Sciarresi; Mitchell Baum; Gerasimos J.N. Danalatos; Elvis F. Elli; Georgios Kalogeropoulos; Kyle King; Caio dos Santos; August Thies; Lia Olmedo Pico; et al. (Field Crops Research, 2023)

Unintended CRISPR-Cas9 editing outcomes: a review of the detection and prevalence of structural variants generated by gene-editing in human cells - John Murray Topp Hunt; Christopher Allan Samson; Alex du Rand; Hilary M. Sheppard (Human Genetics, 2023)
Genome editing using the clustered regularly interspaced short palindromic repeats (CRISPR) and CRISPR-associated protein (Cas) gene-editing system (CRISPR-Cas) is a valuable tool for fundamental and applied research applications. Significant improvements in editing efficacy have advanced genome editing strategies into phase 3 human clinical trials. However, recent studies suggest that our understanding of editing outcomes has lagged behind the developments made in generating the edits themselves. While many researchers have analyzed on- and off-target events through the lens of small insertions or deletions at predicted sites, screens for larger structural variants (SVs) and chromosomal abnormalities are not routinely performed. Full and comprehensive validation of on- and off-target effects is required to ensure reproducibility and to accurately assess the safety of future editing applications. Here we review SVs associated with CRISPR-editing in cells of human origin and highlight the methods used to detect and avoid them.

Transformation of rice with long DNA-segments consisting of random genomic DNA or centromere-specific DNA - Bao H. Phan; Weiwei Jin; Christopher N. Topp; Cathy X. Zhong; Jiming Jiang; R. Kelly Dawe; Wayne A. Parrott (Transgenic Research, 2007)

Integration of the Gene for Carboxin Resistance Does Not Impact the Ustilago maydis -Maize Interaction - Christopher N. Topp; José Ruiz-Herrera; Alfredo D. Martínez-Espinoza; Scott E. Gold (Current Microbiology, 2002)